Conditions for the formation of a non-autonomous phase at the structural deformation of complex vanadium oxides - M. V. Rotermel; T. I. Krasnenko; S. A. Petrova; S. G. Titova (Chimica Techno Acta)
A new previously unknown effect of a reversible transition from a single-phase system to a heterophase system containing a non-autonomous phase was observed during thermal and chemical deformations of the Zn2-2xCd2xV2O7 structure.The role of local symmetry in the formation of the non-autonomous phase is shown on the basis of X-ray diffraction studies in situ and a comparative crystal-chemical analysis of the structural deformations of isoform monoclinic solid solutions of zinc and copper pyrovanadates with zero volumetric thermal expansion.